COVID-19 impact on doctors and health workers - Shrestha, Rabindra Man; Kunwar, Arun Raj (Orthodontic Journal of Nepal, 2020)
The present article probes the current situation of doctors and health workers in Nepal as the impact of COVID-19 pandemic. It mainly discusses the social, occupational and psychological effects on the professionals. The article also documents the global occurrences and data related to COVID-19 pandemic. Lastly, it enlists the key recommendations to decrease the spread of COVID-19 and mental health measures to protect the health of the healthcare workers.